2013
DOI: 10.1016/j.jalz.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive measurement of daily computer use to detect mild cognitive impairment

Abstract: Background Mild disturbances of higher order activities of daily living are present in people diagnosed with mild cognitive impairment (MCI). These deficits may be difficult to detect among those still living independently. Unobtrusive continuous assessment of a complex activity such as home computer use may detect mild functional changes and identify MCI. We sought to determine whether long-term changes in remotely monitored computer use differ in persons with MCI in comparison to cognitively intact volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 37 publications
10
143
1
2
Order By: Relevance
“…One study reported no differences in daily recorded computer activity (based on mouse movements) at baseline between groups of cognitively healthy and MCI participants. However, at follow-up two years and three years later, a significant decrease in number of days with computer use, mean daily use and an increase in day-to-day variability was found in the MCI group only 40. The authors concluded that computer usage is likely to be sensitive to cognitive change due to its reliance on multiple cognitive domains.…”
Section: Presentationmentioning
confidence: 95%
“…One study reported no differences in daily recorded computer activity (based on mouse movements) at baseline between groups of cognitively healthy and MCI participants. However, at follow-up two years and three years later, a significant decrease in number of days with computer use, mean daily use and an increase in day-to-day variability was found in the MCI group only 40. The authors concluded that computer usage is likely to be sensitive to cognitive change due to its reliance on multiple cognitive domains.…”
Section: Presentationmentioning
confidence: 95%
“…Wearable sensors can now monitor tremor for as long as 10 hours daily. 34 Remote measurement of daily computer use can detect mild cognitive impairment, 35 and smartphones can map out the geographic area where individuals with Parkinson disease live. 36 Potentially more powerful applications are on the horizon.…”
Section: Novel Objective and Sensitive Clinical Measures To Detect Efmentioning
confidence: 99%
“…More recently multiple web-based and app-based cognitive assessments have emerged [3] including digitized versions of pen and paper tasks, such as clock drawing [4] including a digital clock-drawing pen [5]. In addition, the manner in which people use technology and changes in their patterns of use has been identified as an early indicator of emerging cognitive impairment [6, 7]. Technological assessment of functional activities extends to tasks such as making tea and toast [8], coffee-making [9], as well as instrumental activities of daily living [10].…”
Section: Introductionmentioning
confidence: 99%